Synthesis, Molecular Modeling, and Biological Activity of Zinc(II) Salts with 1, 4-Bis(benzimidazol-2-yl)benzene. (9th October 2012) - Krishnamurthy, G.
Abstract : Zinc(II) halides and perchlorate react with 1, 4-bis(benzimidazol-2-yl)benzene (L) in 1 : 2 molar ratio in n-butanol/2-methoxy ethanol (10 mL) at refluxing temperature to produce white/pale yellow-colored complexes of the formulae [ZnCl2 L]H2 O, [ZnBr2 L]3H2 O, and [Zn(OClO3 )2 L]HOCH2 CH2 CH2 CH3 . Zinc(II) iodide also reacts with L in 1 : 2 molar ratio in n-butanol (HOCH2 CH2 CH2 CH3 ) to yield white-colored complex of the formula [ZnL2 (OCH2 CH2 CH2 CH3 )2 ]. The complexes were characterized by elemental analysis, molar conductance measurements, thermal analysis, and IR, 1 H-, 13 C-NMR spectral studies. The complexes showed significant anthelmintic activity. The minimum energy configuration has been obtained for the zinc complexes using molecular modeling Pro Plus; a tool developed by ChemSW, inc, USA.